The Dialectic Method: A Critical and Postmodern Alternative to the Scientific Method - Phillip Dybicz; Loretta Pyles (Advances in Social Work, 2011)
This paper introduces Hans-Georg Gadamer's dialectic method and elaborates upon its application to social work inquiry. Its strengths lie in its ability to uncover social constructed truths, to explain human behavior in a non-deterministic manner that emphasizes personal agency and empowerment, and to foster a consciousness-raising process that leads to praxis. This makes it ideally suited for knowledge gathering by practitioners in the field who seek to apply postmodern practice approaches such as the strengths perspective, solution-building therapy, and narrative therapy. Examples are given of its application to both micro and macro practice concerns.